Developing English Beginner Material for Adult Level Integrated into Web Mobile at Stkip PGRI Lubuklinggau - Agus Triyogo; Maria Ramasari; Hamdan Hamdan (Graduate School of Universitas Negeri Malang, 2023)
The purpose of this research is to Produce Beginner English material based on Web Mobile. The method of research was Research and Development with the model of ADDIE. The result shows that based on the judgment from the experts got a score of 3.48, which means the e-model validation was valid. The results of the assessment of student responses to the e-module in the completed questionnaire obtained an average overall assessment score of 3,34 with a very good product category. The outcomes from the research are articles published in national journal indexes by Sinta and an English module based on Web Mobile.